Integration of Local Potential in Project-Based Learning: Its Impact on Critical Thinking and Scientific Attitudes of Students of SMAN 1 Darussalam - Rahmadani; Evi Apriana; Nurlena Andalia; Juli Firmansyah; Ibrahim (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effectiveness of the implementation of the Project-Based Learning (PjBL) model based on local potential on biotechnology material in improving students' critical thinking skills and scientific attitudes. The study used a quantitative approach with a one-group pretest-posttest design for 35 students. The instruments were a critical thinking test and a scientific attitude observation sheet that had been declared valid and reliable (Cronbach's Alpha = 0.789). The results showed a significant increase in critical thinking skills, with an average pretest score of 17.63 increasing to 37.71 in the posttest, and an N-Gain value of 0.897 (high category). The increase occurred in all indicators, with the highest value in the indicator providing simple explanations (0.9226) and the lowest in the indicator organizing strategies and tactics (0.8723), but all in the high category. Students' scientific attitudes also increased, indicated by an average pretest score of 17.49 to 29.51 in the posttest, with an N-Gain value of 0.808 (high category). The highest improvement was found in the critical thinking indicator (0.93), while the lowest was in the collaboration indicator (0.63). Thus, the local potential-based PjBL model effectively improves students' critical thinking skills and scientific attitudes through contextual and project-based learning.